PEMANFAATAN TANAMAN TOGA BAGI KESEHATAN KELUARGA DAN MASYARAKAT - Renny Agus Saktiawan; Atmiasri Atmiasri (Jurnal Abadimas Adi Buana, 2017)
ABSTRACT Medicinal plants are a source of power that has existed since age-old. TOGA used by our ancestors in order to overcome health problems by making various ingredients of medicinal issues. Therefore the use of medicinal plant families or we called TOGA should be developed and circulated in the community, especially for all of households. But many people are still not aware of the utilization of family medicine. People often mistake them for the raw material too produce of traditional medicines and they do not understand yet how to process the material. It can cause side effects that are different for each person if given excessive doses of the drug. Health to our survival is very important, because without health we could not do any activities that can sustain our lifes. The method used observation and documentation. Medicinal plants are all kinds of plants that have their own uses as a medicine. Many parts of the plant can be used, such as the fruit, stems, leaves, and roots or tubers. Processing technology medicinal plants can be done by sorting, alteration, draining, and drying, storage, and so on. While herb processing can be done by grind, boil, and simmer. Keywords: Medicinal plants, TOGA, Benefits, and Processing.